ECONOMICS ON BUSINESS SUSTAINABILITY (STUDY ON MSMES IN MAKASSAR CITY) - ldra Wahyuni; Maghfirah; Zalkha Soraya (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to examine the influence of digital financial literacy and economic literacy on business sustainability (Study on MSMEs in Makassar City). The type of research used in this research is a quantitative survey method. The MSME sample consisted of 100 samples selected using the purposive sampling method. The data in the sample was selected using primary data obtained using a distributed questionnaire. The data analysis methods used are data validation tests, reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests using the SPSS 26 analysis tool. The results of the research show that digital financial literacy and economic literacy have a positive and significant effect on business sustainability in Makassar city.